Analisis Tingkat Kepuasan Pasien Bpjs terhadap Pelayanan Kesehatan - Eprila Bernolyan Putri; Maksuk Maksuk; Sri Utari (Universitas Muhammadiyah Manado, 2026)
Patient satisfaction represents the comparison between expectations before receiving health services and perceptions of the quality of services provided. The assessment of healthcare service quality generally uses the five SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. A preliminary survey showed that the reliability dimension obtained the lowest average score compared to other dimensions. This study employed an observational analytic design with a cross-sectional approach. The study population consisted of BPJS (National Health Insurance) patients who received services. A total of 386 respondents were selected using purposive sampling. Data were collected through a SERVQUAL-based questionnaire and analyzed using univariate, bivariate (chi-square test), and multivariate (logistic regression) analyses to identify the dominant factors related to patient satisfaction. The results indicated that the variables of age (p < 0.05) and all five SERVQUAL dimensions (tangible, reliability, responsiveness, assurance, and empathy) were significantly associated with patient satisfaction levels. It can be concluded that most BPJS patients were satisfied with the services provided. The assurance dimension was found to be the most influential factor. Therefore, efforts to improve service quality should focus on strengthening aspects of assurance, trust, and service reliability.